Job satisfaction and job performance among John B. Lacson Colleges Foundation Teaching Staff in Iloilo City - Caytiles, Cheryl D.; Pulmones, Lorna T.; Sibonga, Ma. Lovella N.; Solidum, Maria Mabel M.
This study determined the job satisfaction and job performance of the John B. Lacson Colleges Foundation teaching staff in Iloilo City. Conducted in February 2004, the participants of this research were 70 randomly selected teaching staff of the JBLCF Molo and Arevalo units. This study utilized the efficiency rating records fled at the dean's offices of the twoncampuses and the results of the prepared questionnaire. Descriptive statistics used is frequency. The inferential statistics used is the Pearson's r. The study revealed that there is no significant correlation beteen work experience and job satisfaction, work experience and job performance, salary and job satisfaction, and salary and job performance when taken as one.